1989
DOI: 10.2105/ajph.79.5.565
|View full text |Cite
|
Sign up to set email alerts
|

Trends in dental fluorosis and dental caries prevalences in Newburgh and Kingston, NY.

Abstract: A study was undertaken in New York State to determine the changes in dental fluorosis prevalence from 1955 to 1986 in fluoridated Newburgh and non-fluoridated Kingston children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 34 publications
1
49
1
Order By: Relevance
“…Indeed, fluorosis was almost absent with only 2.9% of the children examined showing any definite signs of the condition and a Dean's index of 0.1 [Driscoll et al, 1986]. Moreover, Leverett [1986] found a prevalence of 10.1% and Kumar et al [1989] a value of 9.4% and a Dean's score of 0.23. Present data on the prevalence and severity of dental fluorosis recorded in the high-fluoride area were lower than in most studies carried out in other countries.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, fluorosis was almost absent with only 2.9% of the children examined showing any definite signs of the condition and a Dean's index of 0.1 [Driscoll et al, 1986]. Moreover, Leverett [1986] found a prevalence of 10.1% and Kumar et al [1989] a value of 9.4% and a Dean's score of 0.23. Present data on the prevalence and severity of dental fluorosis recorded in the high-fluoride area were lower than in most studies carried out in other countries.…”
Section: Discussionmentioning
confidence: 94%
“…1,2 Epidemiological studies have found differences in fluorosis prevalence among racial/ethnic groups that do not appear to be explained by levels of fluoride intake. [3][4] These provide indirect support for a possible genetic contribution to the etiology of dental fluorosis in humans.…”
Section: Commentary and Analysismentioning
confidence: 93%
“…The determination of case status was based on fluorosis evaluation using Dean's method. Seventy-five of the 240 children were designated as cases based on the presence of very mild to severe fluorosis (grades [2][3][4][5]; 165 children were designated as controls based on categorizations of normal or questionable fluorosis (grades 0-1).…”
Section: Main Outcome Measurementioning
confidence: 99%
“…Dean's index, however, has been adopted for dental fluorosis monitoring by the Chinese Center for Disease Control and Prevention [40], from which we had obtained our data. Dean's index places fluorosis affected teeth into six categories: normal, questionable, very mild, mild, moderate and severe [41]. The formula is as follows: N 4 and N 5 are number of subjects from the categories of normal, questionable, very mild, mild, moderate and severe dental fluorosis, respectively; N is the number of all subjects [42].…”
Section: Collection Of Data On Fluoride Concentrations and Fluorosismentioning
confidence: 99%